2008
DOI: 10.1002/mds.22162
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of motor impairment influences quality of life in Parkinson's disease

Abstract: We evaluated the relationship between upper extremity (UE) and lower extremity (LE) motor impairments in Parkinson's disease (PD) to overall disability and quality of life (QoL) measures. A total of 639 patients who were diagnosed with idiopathic PD were administered the Unified Parkinson's Disease Rating Scale (UPDRS), QoL, activities of daily living (ADL), and behavioral scales. Composite UE and LE scores from the motor section of the UPDRS were correlated with ADL, QoL, and behavioral measurement scores whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 8 publications
0
7
1
3
Order By: Relevance
“…The UPDRS and the H-Y scales may not be sensitive measures to evaluate the impact of disease severity on daily life 1 . In contrast, other studies 9,45,46 found an association between UPDRS scores and quality of life measures. According to Havlikova et al 9 , disease severity evaluated through the UPDRS was a significant predictor of all subscores, except for social support and cognition.…”
Section: Correlationscontrasting
confidence: 63%
“…The UPDRS and the H-Y scales may not be sensitive measures to evaluate the impact of disease severity on daily life 1 . In contrast, other studies 9,45,46 found an association between UPDRS scores and quality of life measures. According to Havlikova et al 9 , disease severity evaluated through the UPDRS was a significant predictor of all subscores, except for social support and cognition.…”
Section: Correlationscontrasting
confidence: 63%
“…A study in Florida in 639 patients with PD showed that all motor impairments generally worsened HRQoL but lower extremity impairments had a larger effect than upper extremity impairments. 59 As indicated above, a common, and often the first type of motor fluctuation to develop during treatment, is an end-of-dose wearingoff. 60 As the name implies, the patient develops a loss of response to a dose of medication before taking the next dose.…”
Section: The Patient's Perspectivementioning
confidence: 99%
“…Of note, Nocera et al recently identified a significant positive correlation between lower extremity strength and GI performance [6]. Conversely, impaired lower extremity strength has been shown to negatively influence functional mobility and patient perceived quality of life [7,8]. Thus, treatment modalities that enhance lower extremity strength may have important therapeutic ramifications.…”
Section: Introductionmentioning
confidence: 96%